Pediatric oncology healthcare professionals’ attitudes to and awareness of regulations for minors’ and guardians’ online record access: a mixed-methods study in Sweden - Hagström, Josefin; Blease, Charlotte; Harila, Arja; Scandurra, Isabella; Lähteenmäki, Päivi; Hägglund, Maria (BioMed Central, 2026)
Background
Healthcare providers and policymakers worldwide differ in their provision of access to adolescent patients’ electronic health records (EHR). The regulatory framework in Sweden restricting both guardians’ and adolescents’ online record access (ORA) has during recent years received criticism. The aim was to quantitatively and qualitatively, explore attitudes about ORA and perceptions about ORA regulations among pediatric oncology healthcare professionals (HCPs) in Sweden.
Methods
A convergent mixed-methods design (QUAL, quan) was used, consisting of a survey study (N = 95) and semi-structured individual interviews (N = 13). Physicians and nurses in pediatric oncology were recruited in clinics face-to-face or via staff e-mail. Descriptive statistics were used to present quantitative survey results. Interviews were recorded, transcribed, and analyzed using content analysis.
Results
A majority of participants (72%) were critical of the access restrictions but lacked knowledge about access extensions, with more than 60% unaware of application procedures. Five themes emerged regarding both perceived benefits and risks of ORA. Examples of benefits included adolescent empowerment, parental support, and improved partnership; risks included an increased emotional distress and confusion among young patients and their guardians, increased workload for HCPs, and threats to adolescent confidentiality. An additional five identified themes captured HCPs’ views on regulations and included uncertainty, variation among adolescents, and the need to balance parental support and adolescent privacy.
Conclusions
Findings indicate lacking knowledge about ORA regulations and little incentive for HCPs to promote its use. While risks of ORA were often directly experienced and concerned confidentiality breaches and difficulties with EHR documentation, benefits tended to be anticipatory and related to patient or parent experiences. Still, HCPs showed limited support for ORA restrictions during adolescence. To ensure safe and effective ORA use, HCPs need clearer guidance and support.